Desenvolvimento de uma plataforma de comunicação para monitoramento das variáveis de um sistema de geração distribuída do tipo fotovoltaico através do uso de tecnologias sem fio e dispositivos planares - Azevêdo, Pablo Lucian Cardoso de (Universidade Federal Rural do Semi-Árido, 2020)
With the growing increase in solar photovoltaic plants, it becomes necessary to obtain variables related to their generation capacity and to transmit these data. For this work, a communication platform will be developed to obtain, store and transmit the parameters of an electricity generation system using photovoltaic solar energy, such as solar radiation levels and operating temperature in the solar panels of the Mossoró II plant installed. at the Federal Rural University of Semiarid. During the work, the prototype project will be demonstrated, which will be divided into two stages, one focused on the acquisition of these parameters and the other for the communication system where data transmission via radio frequency will occur. For this study, the Arduino prototyping platform will be used, responsible for the interconnection of the parts of data acquisition and transmission through radio frequency. To send the data, the NRF24L01 transceiver was adopted, whose operating frequency is within the 2.4 GHz ISM band, with which a planar Yagi antenna was designed. The results of the simulations were obtained using the ANSYS HFSS® software. The results of the simulations reached the characteristics of the application, since the loss of return of the antenna presented conformity with the frequency range of the transceiver, in relation to radiation characteristics the antennas had directional radiation diagram and a gain of approximately 8.71 dB. The experimental result of the loss of return was in accordance with the values and behavior, but with a slight shift in the resonance frequency, which at practical levels does not interfere with anything in the application of the antenna. After that, the antenna was implemented in the transceiver performing a range test in order to verify the communication of the devices, presenting a satisfactory result, in this way the system was implemented and acquired the influencing parameters of a solar photovoltaic system
Keywords: Telemetria; Antena impressa; Yagi-Uda; Quase-Yagi; Sistema de comunicação; Energia solar fotovoltaica; Telemetry; Printed antenna; Yagi-Uda; Quasi-Yagi; Communication system; Photovoltaic solar energy; ENGENHARIAS::ENGENHARIA ELETRICA